2019
DOI: 10.1016/j.jmig.2018.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Surgical, Clinical, and Functional Outcomes in Patients with Rectosigmoid Endometriosis in the Gray Zone: 13-Year Long-Term Follow-up

Abstract: To compare long-term surgical, clinical, and functional outcomes between conservative and radical surgery in patients with rectosigmoid endometriosis (RSE) and preoperative intermediate risk of segmental resection. Design: Retrospective cohort study (Canadian Task Force classification II-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 28 publications
1
49
1
2
Order By: Relevance
“…Among the 41 articles included in the review (Table 1) [11,20−59], 37 were excluded from the meta-analysis according to the inclusion criteria: eleven were excluded because of a follow-up period <12 months and 26 on the basis of the definition of recurrence (either nonspecified or without follow-up surgery with histologic proof of recurrence). In total, 41 studies were retained for the systemic review [11,20−59], 4 of which were included (Table 2) [21,25,30,47] in the meta-analysis ( Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 41 articles included in the review (Table 1) [11,20−59], 37 were excluded from the meta-analysis according to the inclusion criteria: eleven were excluded because of a follow-up period <12 months and 26 on the basis of the definition of recurrence (either nonspecified or without follow-up surgery with histologic proof of recurrence). In total, 41 studies were retained for the systemic review [11,20−59], 4 of which were included (Table 2) [21,25,30,47] in the meta-analysis ( Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…When considering all included studies (n = 41) [11,20−59], no significant difference in overall recurrence was found among the 3 surgical groups, with ORs of 1.47 (95% CI, 0.89−2.43; I 2 = 72%; p = .7) ( Fig. 2A) [21,22,24,25,27,30,47,53], 1.08 (95% CI, 0.59−1.98; I 2 = 0%; p = .95) ( Fig. 2B) [21,25,35,40,47,53,59], and 1.21 (95% CI, 0.62−2.35; I 2 =57%; p = .58) ( Fig.…”
Section: Overall Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…In general, radiological techniques can be used to establish the presence and extent of rectosigmoid endometriosis, particularly when there is suspicion of disease despite negative ultrasonographic findings and/or of the presence of multifocal disease with sigmoid or upper intestinal nodules. Moreover, in order to plan surgery, nowadays the role of radiologic imaging still remains relevant and many patients with clinical suspicion of rectosigmoid endometriosis are routinely referred to radiologists for the diagnosis of intestinal endometriosis [20,21].…”
Section: Introductionmentioning
confidence: 99%